2005
DOI: 10.1152/ajpheart.00080.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol exposure impairs angiogenesis and the proliferative phase of wound healing

Abstract: Acute ethanol exposure represents an increased risk factor for morbidity and mortality associated with surgical or traumatic injury. Despite clinical observations suggesting that ethanol exposure before injury alters tissue repair processes, little direct evidence about the mechanism by which ethanol affects the wound healing process is available. In this study, excisional wounds from female BALB/c mice with or without circulating ethanol levels of 100 mg/dl were used to assess wound closure, angiogenesis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 43 publications
(54 reference statements)
9
99
0
2
Order By: Relevance
“…However, higher dose at 10% EtOH inhibit angiogenesis. Inhibition of angiogenesis has also been reported in studies carried out on chick embryo and on wound healing (Radek, Matthies et al 2005;Radek, Kovacs et al 2008). This suggests that EtOH inhibit the angiogenesis at higher doses.…”
Section: Discussionmentioning
confidence: 76%
“…However, higher dose at 10% EtOH inhibit angiogenesis. Inhibition of angiogenesis has also been reported in studies carried out on chick embryo and on wound healing (Radek, Matthies et al 2005;Radek, Kovacs et al 2008). This suggests that EtOH inhibit the angiogenesis at higher doses.…”
Section: Discussionmentioning
confidence: 76%
“…After 8 h, the ethanol media was replaced with fresh ethanol-free media, and the cells incubated for another 8 h. The cells were then trypsinized and incubated on an elliptical rotator at a concentration of 5 ϫ 10 5 for 30 min at room temperature with media in the presence or absence of 100 ng/ml of murine VEGF 164 (mVEGF164) (R&D Systems, Minneapolis, MN). Following incubation, cord formation was assessed as described previously (30,40). For each independent experiment, the number of endothelial cordlike structures formed in the presence of control mVEGF 164 was considered maximal (100%), and experimental values were determined as a percentage of maximal cord formation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in our laboratory demonstrated that mice with a blood alcohol concentration (BAC) of 0.1% (100 mg/dl) at the time of injury exhibited a 50% reduction in wound vascularity (40). The reduction in vascularity occurred even though the level of VEGF in the wounds from ethanol-exposed mice was greater than that of control.…”
mentioning
confidence: 96%
“…Relevant murine models demonstrate that acute alcohol consumption decreases the expression of VEGF receptors and reduces nuclear expression of HIF-1α in endothelial cells, thereby affecting angiogenesis and the proliferative phase of wound healing [69,70]. There are also studies showing that inappropriate alcohol consumption has an adverse effect on the physiologic reepithelialisation and collagen production [69][70][71][72].…”
Section: Inappropriate Alcohol Consumption Is Linked To Non-physiologmentioning
confidence: 99%